2012
DOI: 10.1002/ejoc.201201325
|View full text |Cite
|
Sign up to set email alerts
|

Explanation of Different Regioselectivities in the ortho‐Lithiation of Ferrocenyl(phenyl)methanamines

Abstract: Diastereoselective ortho‐lithiation of ferrocenes is a principal strategy for the synthesis of chiral ferrocene ligands. Dilithiation of (R)‐1‐(2‐bromophenyl)‐1‐ferrocenyl‐N,N‐dimethylmethanamine leads to a dilithium intermediate, which can be transformed to a Taniaphos ligand with (R,Rp)‐configuration. On the other hand, lithiation of (R)‐1‐phenyl‐1‐ferrocenyl‐N,N‐dimethylmethanamine affords a lithiated product with opposite configuration of the stereogenic plane. Presumably, the second lithium atom attached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…In the C ‐lithiated isomer syn ‐ 13 a positive overlap is observed between the lithium atom and the nearest carbon atoms C1 and C17 of both cyclopentadienyl rings and the Fe atom. A similar Li–Fe interaction was computationally predicted in other derivatives too 28. The shift of the Li atom to an oxygen atom results in shortening of the LiFe distance and thus the overlap of both atoms and the stabilizing interaction increases.…”
Section: Resultssupporting
confidence: 69%
“…In the C ‐lithiated isomer syn ‐ 13 a positive overlap is observed between the lithium atom and the nearest carbon atoms C1 and C17 of both cyclopentadienyl rings and the Fe atom. A similar Li–Fe interaction was computationally predicted in other derivatives too 28. The shift of the Li atom to an oxygen atom results in shortening of the LiFe distance and thus the overlap of both atoms and the stabilizing interaction increases.…”
Section: Resultssupporting
confidence: 69%
“…The configuration of the resulting diphosphine contradicts the stereochemistry predicted by the classical model of ferrocenylethanamine ortho ‐lithiation . We have shown that it proceeds via a dilithiated ferrocenyl(phenyl)methanamine intermediate, which is stabilized through the formation of an intramolecular C 2 Li 2 arrangement and possibly also by an intramolecular Fe–Li bond . Recently, we have studied the retro‐Brook rearrangements of (ferrocenylalkyloxy)silanes .…”
Section: Introductionmentioning
confidence: 69%
“…As shown in Figure 2, out of the 50 ligands tested in the reaction, the three ligands providing the highest enantiomeric excess were ROPhos, [19] Tania-phos T001, [20] and (2 R ,5 R )-1-{[(2 R ,5 R )-2,5-diphenylpyrrolidin-1-yl]methylene}-2,5-diphenylpyrrolidinium tetrafluoroborate ( L2 ) [21] (Figure 3). With BBA as the borylating agent, ( R,S )-Josiphos, which proved successful for the addition of B 2 pin 2 , was not effective in the borylation of α , β -unsaturated amides, and led to a trifluoroboratoamide with modest yield and enantiomeric ratio.…”
Section: Resultsmentioning
confidence: 99%